(untitled) (Heritage, 2025)
Yugoslav-Albanian economic relations developed intensively in the 1920s and 1930s. The two neighboring states organized trade and border traffic, given the fact that the population on both sides of the border line depended on each other for trade in essential items. After the end of World War II, the previous agreements on trade and the circulation of goods were mostly accepted. The Yugoslav side sought to bind Albania to itself and tear it away from, primarily, Italian influence. Economic cooperation on the Yugoslav side implied the position that Albania was an area of special interest. Restoring economic ties with Albania, providing personnel assistance, and charting the course of Albanian foreign trade were priorities for Yugoslavia. The problems that the Yugoslav authorities, primarily the Ministry of Trade and Supply, encountered in border trade were the undefined and often uncontrolled crossing of so-called rationed goods, which gave room for smuggling and speculation. The Ministry of Trade and Supply managed to regulate the circulation of rationed goods, balancing the legal framework and the needs of the local population, involving other competent ministries, as well as republican authorities, in the implementation of the measures.